Copenhagen Psychosocial Questionnaire (COPSOQ) - Psychometric properties of selected scales in the Polish version - Maria Widerszal-Bazyl (Nofer Institute of Occupational Medicine, 2017)
Background: The Copenhagen Psychosocial Questionniare (COPSOQ) has many advantages as compared to other similar instruments, i.a., it is not related to one single theoretical model and it measures a wide spectrum of psychosocial working conditions that have shown proven impact on health. The aim of the article is to summarize information on psychometric properties of 11 scales in the Polish version: Quantitative Demands, Emotional Demands, Influence at Work, Social Support, Possibilities for Development, Meaning of Work, Role Clarity, Quality of Leadership, Job Insecurity, Job Satisfaction, and General Health. Material and Methods: Analyses were based on the results of 4 research projects, in which the Polish version of the COPCOQ scales has been used: on a representative sample of Polish nurses (N = 4354), job insecurity in 2 groups of civil servants (N = 295, N = 724), mobbing among teachers (N = 1037) and psychological consequences of restructuring (N = 1396). The following psychometric characteristics were analysed: internal reliability, theoretical validity, and factorial validity. Results: Internal reliability of the following 8 scales was found satisfactory: Quantitative Demands, Influence at Work, Social Support, Possibilities for Development, Meaning of Work, Quality of Leadership, Job Satisfaction, and General Health (Cronbach's α = 0.7-0.91, depending on the scale). The results of exploratory factor analyses indicated factorial separateness of the above mentioned scales. Theoretical validity of 11 scales was confirmed; they were associated with variables that can be regarded as their validity criteria. Conclusions: The 8 COPSOQ scales, in the Polish version, can be recommended for using in the research involving psychosocial job characteristics. Mean scores on these scales and standard deviations given in the article can serve as reference points during an evaluation of received results. Med Pr 2017;68(3):329-348